2018
DOI: 10.1038/s41598-018-20632-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of siRNA lipid nanoparticles: Fate in the GI tract

Abstract: Oral delivery, a patient-friendly means of drug delivery, is preferred for local administration of intestinal therapeutics. Lipidoid nanoparticles, which have been previously shown to deliver siRNA to intestinal epithelial cells, have potential to treat intestinal disease. It is unknown, however, whether the oral delivery of these particles is possible. To better understand the fate of lipid nanoparticles in the gastrointestinal (GI) tract, we studied delivery under deconstructed stomach and intestinal conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 58 publications
0
64
0
Order By: Relevance
“…This is in stark contrast with the several hundreds of published articles relative to protein-NPs interactions in blood [3]. It has been recently shown that high, but not low, pepsin concentrations can induce aggregation of lipid NPs, hindering the delivery of encapsulated siRNA to Caco-2 cells [15]. Di Silvio et al demonstrated that upon simultaneous in vitro digestion of magnetite NPs and bread, a PC builds upon the NPs.…”
Section: What Is It Known So Far?mentioning
confidence: 96%
“…This is in stark contrast with the several hundreds of published articles relative to protein-NPs interactions in blood [3]. It has been recently shown that high, but not low, pepsin concentrations can induce aggregation of lipid NPs, hindering the delivery of encapsulated siRNA to Caco-2 cells [15]. Di Silvio et al demonstrated that upon simultaneous in vitro digestion of magnetite NPs and bread, a PC builds upon the NPs.…”
Section: What Is It Known So Far?mentioning
confidence: 96%
“…Mucin at a 2% w/v concentration in Caco‐2 cell buffer was also found to drastically reduce silencing potential (90–40%). LNPs stay in the mouse GI tract for 8 hours after delivery, and fluorescently labeled siRNA was found in mouse intestinal cells; however, the gene silencing of GAPDH in vivo was not statistically significant . The low in vivo efficacy may be due to spotty uptake.…”
Section: Oral Delivery Systemsmentioning
confidence: 98%
“…However, liposome delivery is complicated by concerns for toxicity and requires improvement in efficacy. Ball et al . made lipoid nanoparticles (LNPs) made of amphiphilic lipid‐like materials, which when complexed with cholesterol, distearoyl‐sn‐glycerol‐3‐phosphocholine, and PEG‐lipid form the nanoparticles.…”
Section: Oral Delivery Systemsmentioning
confidence: 99%
“…The most active lipidoids in the silencing of glyceraldehyde 3-phosphate dehydrogenase (GAPDH) in human colorectal adenocarcinoma (Caco-2) cells were 94b, 94d and 94f. 206,207 The 3-tailed version of 94b was also applied in the silencing of the anti-apoptotic protein Mcl1, which resulted in apoptosis of mantle cell lymphoma cells, 208 and of tumor necrosis factor α in a macrophagefibroblast model for diabetic foot ulcers. 209 In another combinatorial approach, amines were reacted with racemic alkyl epoxides of varying tail lengths (Scheme 2B) to give the substituted aminoalcohol products 95 as mixtures of diastereomers.…”
Section: Lipidoidsmentioning
confidence: 99%